Multi-vehicle decentralized fusion and tracking - El-Fallah, A.; Zatezalo, A.; Mahler, Ronald; Mehra, R. (2012)
In this paper, we introduce a decentralized fusion and tracking based on a distributed multi-source multitarget filtering and robust communication with the following features: (i) data reduction; (ii) a disruption tolerant dissemination procedure that takes advantage of storage and mobility; and (iii) efficient data set reconciliation algorithms. We developed and implemented complex high-fidelity marine application demonstration of this approach that encompasses all relevant environmental parameters. In the simulated example, multi-source information is fused by exploiting sensors from disparate Unmanned Underwater Vehicles (UUV) and Unmanned Surface Vehicle (USV) multi-sensor platforms. Communications among the platforms are continuously establishing and breaking depending on the time-changing geometry. We compare and evaluate the developed algorithms by assessing their performance against different scenarios. © 2012 Copyright Society of Photo-Optical Instrumentation Engineers (SPIE).